2010
DOI: 10.1111/j.1742-1241.2008.01750.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of early atherosclerotic changes in acromegalic patients

Abstract: In active acromegalics, early atherosclerotic changes are not only attributed to the high prevalence of risk factors, but also to the abnormal GH secretion itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 25 publications
(30 reference statements)
2
20
1
1
Order By: Relevance
“…Similarly, Baykan et al [9] evaluated patients with acromegaly and reported decreased FMD in acromegaly. Moreover, some studies revealed that patients with active acromegaly had significantly decreased FMD compared to controls [10,11]. Significant improvements in endothelial dysfunction after transsphenoidal surgery or GH receptor antagonist therapy in patients with acromegaly were found in other previous studies [29,30].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, Baykan et al [9] evaluated patients with acromegaly and reported decreased FMD in acromegaly. Moreover, some studies revealed that patients with active acromegaly had significantly decreased FMD compared to controls [10,11]. Significant improvements in endothelial dysfunction after transsphenoidal surgery or GH receptor antagonist therapy in patients with acromegaly were found in other previous studies [29,30].…”
Section: Discussionmentioning
confidence: 90%
“…Impaired flow mediated dilatation (FMD), which is a marker of endothelial dysfunction has been demonstrated as an early marker of atherosclerosis [6]. Endothelial dysfunction and carotid intima media thickness (CIMT) have been explored in several studies performed in patients with acromegaly [7][8][9][10][11]. Epicardial adipose tissue is located around the heart, especially around the major coronary vessels, and previous studies have shown that increased epicardial adipose tissue thickness (EAT) is associated with CAD and major adverse cardiac events [12].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, specific assessments of carotid and coronary artery disease in patients with acromegaly have yielded mixed results. For example, Kartal et al [36] and Brevetti et al [12] observed an increase in carotid intima-media thickness in active acromegaly, whereas others have reported no significant increase [37]. Early post-mortem studies suggested an increase in coronary artery atherosclerosis [38,39].…”
Section: Cardiovascular Complicationsmentioning
confidence: 99%
“…Kartal [20] Sakai [22] Octreotide sc, octreotide LAR, and lanreotide SR treatments have all been reported to improve acromegalic cardiomyopathy. However, a recent meta analysis demonstrated that there is more evidence for beneficial cardiac effects with octreotide than with lanreotide [34].…”
Section: Somatostatin Analoguesmentioning
confidence: 98%
“…Kartal [20] Significantly ; IMT compared with controls (patients with acromegaly n = 21; controls n = 282)…”
Section: Somatostatin Analoguesmentioning
confidence: 98%